Characterization of selected Harbin red sausages on the basis of their flavour profiles using HS-SPME-GC/MS combined with electronic nose and electronic tongue. (February 2021) - Yin, Xiaoyu; Lv, Yichao; Wen, Rongxin; Wang, Yan; Chen, Qian; Kong, Baohua
Abstract: In this study, volatile profiles and taste properties of Harbin red sausages prepared with traditional and conventional processing methods were evaluated using solid-phase microextraction gas chromatography–mass spectrometry (SPME-GC/MS) coupled with electronic nose (E-nose) and electronic tongue (E-tongue). Four varieties of traditional sausages and four varieties of conventional sausages were selected. A total of 131 volatiles were identified, of which 50 were found in all sausages, and of which 77 were significantly different between traditional sausages and conventional sausages. The total contents of aldehydes (211.32 μg/kg), ketones (404.28 μg/kg), phenols (1795.40 μg/kg) and furans (928.73 μg/kg) in the traditional sausages were significantly higher than those in the conventional sausages ( P < 0.05). The results of GC/MS coupled with E-nose based on principal component analysis could discriminate the sausages well, but the E-tongue could not clearly distinguish them. The results of partial least square regression ( P < 0.05, Q 2 = 0.659) indicated that there was a high correlation between the E-nose sensors and volatiles of Harbin red sausages. Highlights: A total of 131 volatile compounds were identified in all selected sausages. Seventy-seven volatiles were different between traditional and conventional sausages. The total contents of aldehydes and phenols were higher in the traditional sausages. The E-nose and GC/MS differentiated traditional and conventional sausages well. There was a high correlation between the E-nose sensors and the GC/MS data.